Pengaruh Kompetensi Pegawai, Disiplin Kerja, dan sarana Prasarana Terhadap Efektivitas Pelayanan Publik di Balai Desa Jubang Kecamatan Bulakamba Kabupaten Brebes - Yuyun L Sinaga; Nur Khojin; Muhammad Syaifulloh (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to determine and analyze the influence of Employee Competence, Work Discipline, and Facilities and Infrastructure on the Effectiveness of Public Services at the Jubang Village Hall, Bulakamba District, Brebes Regency. The type of research applied is associative research (explanatory research) with a quantitative approach. The population in this study is the people of Jubang Village who are in the age range of 20 to 49 years with a total of 2,889 people. Based on calculations using the Slovin formula with a 5% leniency level, the official research sample size was 352 respondents determined through a simple random sampling technique. Primary data collection was carried out directly by distributing questionnaire instruments that had been tested for validity and reliability. The data analysis method used to test the hypothesis was Multiple Linear Regression Analysis with the help of SPSS software. The results of partial testing (t-test) showed that Employee Competence had a positive and significant effect on the Effectiveness of Public Services with a calculated t-value of 11.612 and a significance of 0.000 <0.05. The Work Discipline variable was also proven to have a positive and significant influence on Public Service Effectiveness with a calculated t-value of 8.745 and a significance level of 0.000 <0.05. Furthermore, Infrastructure had a positive and significant influence on Public Service Effectiveness with a calculated t-value of 16.773 and a significance level of 0.000 <0.05. Simultaneously (F-test), the three independent variables together had a significant influence on Public Service Effectiveness with a calculated F-value of 181.409 and a significance level of 0.000. The results of this study also confirm that Infrastructure is the variable that provides the most dominant contribution to Public Service Effectiveness at Jubang Village Hall, achieving the highest Standardized Beta Coefficients value of 0.564.